Islamic Variant of Sasak: Transition and Dialectics in the Wetu Telu Community in Lombok, Indonesia - Retno Sirnopati; Abdul Rasyad; Ahmad Tohri (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2022)
Outsiders have often perceived the Wetu Telu community in Lombok as a variant or a splinter of the predominantly Islamic Sasak society's religious system. This article aims to understand the existence of the Wetu Telu community on the island of Lombok from the perspective of both outsiders and insiders with a holistic, interdisciplinary approach. This study uses a qualitative method with a phenomenological approach. The research subjects include the Wetu Telu community in and around Lingsar Narmada in West Lombok, the Tanjung area, and several villages in the Bayan district of North Lombok, such as Loloan, Anyar, Akar-Akar, and Mumbul Sari. The required data were collected through observation, in-depth interviews, documentation, and literature studies. Data analysis involved domain, taxonomic, componential, and thematic analysis. The results show that phenomenologically Wetu Telu is a variant of Islamic Sasak that believes in some Islamic doctrinal values, understands and practices religious rituals that have many similarities with the belief systems before the coming of Islam to Lombok and blends with local Sasak cultural traditions or customs. Wetu Telu was born from the historical transition of the development of local belief systems that dialectically interacted with the arrival and development of major religions on the island of Lombok and were intertwined with the socio-cultural and socio-political dynamics of Sasak society. This study significantly contributes to the study of the relationship between “foreign religion” and local culture with a special reference to the Wetu Telu of Sasak people in Indonesia.